Enhanced effects of walnut green husk solution on the phytoextraction of soil Cd and Zn and corresponding microbial responses. (February 2022) - Liu, Xing; Wu, Yingxin; Lu, Yang; Liu, Xiaowen; Liu, Junjun; Ren, Jie; Wu, Wencheng; Wang, Yuntao; Li, Jie
Abstract: Walnut green husk (WGH) is a common agricultural waste, but it may be conducive to phytoremediation of heavy metals owing to its abundant phenolic hydroxyl, carboxyl, and other functional groups. In this study, WGH solution was used as an enhancer in the phytoextraction process via Sedum plumbizincicola, a hyperaccumulator of Zn and Cd. Microbial responses in the soil and plants were seamlessly analyzed to determine the underlying mechanisms of heavy metal extraction in this process. The results showed that the addition of 0.05 g/mL WGH solution increased the accumulation of Cd (by 153%) and Zn (by 220%) in plants as well as the availabilities of Cd (by 29.46%) and Zn (by 9.71%) in the soil, which can be attributed to an increase in the relative abundance of plant growth-promoting rhizobacteria that benefit phytoextraction. Furthermore, co-occurrence network analysis indicated the keystone taxa in the microbial community. Particularly, one of the keystone taxa, Pseudomonas, was also identified as distinct taxon in soil, and it was dominant among the endophytic bacteria. These results indicated that Pseudomonas, a taxon responded to WGH solution, may play a key role in enhanced phytoextraction in both soil and plant root. These results help to a better understanding of the microbial mechanisms for heavy metal accumulation in hyperaccumulator. Graphical abstract: Image 1 Highlights: WGH solution enhanced Sedum plumbizincicola extraction of Cd (153%) and Zn (220%). WGH solution promoted the growth of PGPR. The underlying responses of soil microbials and endophytes were elucidated.